Infliximab crystal structures reveal insights into self-association. Issue 5 (4th July 2017) - Lerch, Thomas F.; Sharpe, Penelope; Mayclin, Stephen J.; Edwards, Thomas E.; Lee, Eunhee; Conlon, Hugh D.; Polleck, Sharon; Rouse, Jason C.; Luo, Yin; Zou, Qin
ABSTRACT: Aggregation and self-association in protein-based biotherapeutics are critical quality attributes that are tightly controlled by the manufacturing process. Aggregates have the potential to elicit immune reactions, including neutralizing anti-drug antibodies, which can diminish the drug's efficacy upon subsequent dosing. The structural basis of reversible self-association, a form of non-covalent aggregation in the native state, is only beginning to emerge for many biologics and is often unique to a given molecule. In the present study, crystal structures of the infliximab (Remicade) Fc and Fab domains were determined. The Fab domain structures are the first to be reported in the absence of the antigen (i.e., tumor necrosis factor), and are consistent with a mostly rigid complementarity-determining region loop structure and rotational flexibility between variable and constant regions. A potential self-association interface is conserved in two distinct crystal forms of the Fab domain, and solution studies further demonstrate that reversible self-association of infliximab is mediated by the Fab domain. The crystal structures and corresponding solution studies help rationalize the propensity for infliximab to self-associate and provide insights for the design of improved control strategies in biotherapeutics development.